ARE YOU HURTING? FACTORS ASSOCIATED WITH PROXY REPORTED PAIN SEVERITY IN COMMUNITY-DWELLING PERSONS WITH DEMENTIA. (11th November 2018) - Block, P; Hilgeman, M; Collins, A; Allen, R; Kunik, M; Snow, A
Abstract: Under-recognized pain is associated with agitation and poor outcomes in persons with dementia (PWD). The present study examined factors related to caregiver's proxy reported pain severity in a sample of 36 community-dwelling veterans with dementia and their caregivers, participating in a telephone-based intervention study. Caregivers were 86% female and 28% Black with a mean age of 63.06 years, and PWD were 96% male and 23% Black with a mean age of 74.08 years. Results indicated a strong concordance between caregiver/proxy and PWD self-reported pain severity (r = .718, p < .001). Additionally, caregiver/proxy reports of pain severity were significantly associated with caregivers' own level of mindfulness (r = .380, p = .022) as well as the caregivers' proxy reports of the PWD's depression, quality of life, and stress level (r = .504, p = .002; r = -.434, p = .008; r = .339, p = .046, respectively). PWD's self-reported pain was significantly related to caregivers' proxy reported depression and quality of life (r = -.445, p = .023; r = .504, p = .009, respectively), but unrelated to perceived stress (p > .10). The PWD's cognitive status (measured by the Montreal Cognitive Assessment) and caregiver burden were not related to pain severity in this sample (p's > .5). Results suggest that the factors associated with caregivers' proxy reports of pain are complex. Further research is needed to better understand the factors contributing to caregiver/proxy reports of PWD pain severity in order to support caregivers in managing pain in PWD.